Reduced-Complexity Receiver for Free-Space Optical Communication over Orbital Angular Momentum Partial-Pattern Modes - Alaa ElHelaly; Ahmed H. Mehana; Mohammad M. Khairy (International Journal of Antennas and Propagation)
This paper explores the effect of a partial-pattern receiver for transmitted orbital angular momentum (OAM) multimodes included in the Laguerre-Gaussian beam propagating under non-Kolomogorov weak-to-moderate turbulence on the achievable capacity and the error rates with introduced controlled parameters. We deduce the necessary conditions for reducing the receiver’s area to guarantee that the modes are decoupled when the area is reduced. Furthermore, we derive the conditions at which area reduction yields a performance gain over the complete-area reception. For that, some use cases are introduced and discussed and the basic building block for multibeam MIMO receivers with a reduced area is developed and analyzed.